IMPLEMENTASI KEBIJAKAN PEMETAAN TEMATIK DALAM PEMBERIAN HAK GUNA USAHA PADA KANTOR WILAYAH BADAN PERTANAHAN NASIONAL PROVINSI KALIMANTAN TIMUR - Ade Chandra Wijaya (Jurnal Paradigma (JP), 2017)
The aim of this research is to describe and analyze the implementation of thematic mapping policy for granting cultivating right title at the Regional Office of the National Land Agency for East Kalimantan Province related to goals and policy objectives, resources, communication between the organization, the characteristics of the implementing agency, the attitude of the implementers, and economic, social, and political environment. The results showed that the implementation of thematic mapping policy goals for granting cultivation right title at the Regional Office of the National Land Agency for East Kalimantan Province is to provide thematic data as information in making a decision on granting a cultivating right title